Gyrokinetic simulations of toroidal Alfvén eigenmodes excited by energetic ions and external antennas on the Joint European Torus. (21st December 2018) - Aslanyan, V.; Taimourzadeh, S.; Shi, L.; Lin, Z.; Dong, G.; Puglia, P.; Porkolab, M.; Dumont, R.; Sharapov, S.E.; Mailloux, J.; Tsalas, M.; Maslov, M.; et al.
Abstract: The gyrokinetic toroidal code (GTC) has been used to study toroidal Alfvén eigenmodes (TAEs) in high-performance plasmas. Experiments performed at the Joint European Torus (JET), where TAEs were driven by energetic particles arising from neutral beams, ion cyclotron resonant heating, and resonantly excited by dedicated external antennas, have been simulated. Modes driven by populations of energetic particles are observed, matching the TAE frequency seen with magnetic probes in JET experiments. A synthetic antenna, composed of one toroidal and two neighboring poloidal harmonics has been used to probe the modes' damping rates and quantify mechanisms for this damping in GTC simulations. This method was also applied to frequency and damping rate measurements of stable TAEs made by the Alfvén eigenmode active diagnostic in these discharges.